The Connection of Finns’ Environmental Awareness to Their Anticipatory Competence - Ratinen, Ilkka; Linnanen, Lassi (Frontiers in Education, 2022)
Knowledge of people’s abilities must be adapted to a new, sustainable society. Through sustainability competences, the necessary changes in people’s behavior in the pursuit of a sustainable society can be intensified. In this study, Finns (n = 2006) express their knowledge of climate change and biodiversity loss and evaluate their own anticipatory competence. The connection between their environmental awareness and the future’s orientation toward a society of sustainable actions will be studied by statistical analysis. The study discusses how learning sustainability competences can be promoted in science education and reveals the gap between females and males in their objectives for a sustainable future. Finns with higher education have greater environmental awareness than those with lower education. The connection between Finns’ environmental awareness and their structural skills for making a more sustainable future is quite clear.